PENERAPAN PROJECT BASED LEARNING DALAM UPAYA MENGEMBANGKAN KEMAMPUAN BERPIKIR KREATIF MAHASISWA - Alberth Supriyanto Manurung; Edwita E; Zulela S; Gusti Yarmi (Universitas Negeri Medan, 2022)
This study aims to describe the application of project based learning in an effort to develop creative thinking skills of PGSD FKIP students at Esa Unggul University in the Elementary Mathematics Learning course. Data collection techniques used in the form of: a) the method of observation or observation. b) interview method, interviews were conducted as a way to obtain the information needed by researchers by interviewing several students. c) documentation method, this method is used to obtain data about lecturer learning tools in the form of RPS and PjBL activity steps carried out by students in the form of photos. One of the advantages of the project-based learning model is that it is able to train students in using projects/activities as media. This method requires students to be able to explore, assess, interpret, synthesize, and provide information to produce various forms of learning outcomes. With the application of project based learning, creative thinking skills can develop, because the creative thinking skills observed in this study are the ability to identify, analyze, solve problems, think logically and make decisions correctly and can draw conclusions.